Continuous Economic Education as Educational Problem - L. B. Bakhtigulova (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The review of the monograph “Scientific basis of development of continuous economic education in the system of professional education” by T. Yu. Lomakina and M. G. Sergeyeva, published in 2015, provides the idea about the content of the publication devoted to continuing education - topical issue discussed in many scientific papers and the RF Law “On education in the Russian Federation.” Under review are scientific concept, justifying the need of formation of economic competence at various levels of professional education that reflects the essence of the principle of economic competence. The results of experimental verification of the author’s method “Training firm” are described.